Walking with Peety [large type] : the dog who saved my life - O'Grey, Eric; Dagostino, Mark (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Eric was 150 pounds overweight and depressed. After a lifetime of failed diets and the onset of type 2 diabetes, he went to a doctor who surprisingly prescribed a shelter dog. And that's when Eric met Peety: an overweight, middle-aged, and forgotten dog. The two adopted each other and began an incredible journey together that forever changed their lives.